Geothermal history of the Karoo Basin in South Africa inferred from magnetic studies - Maré, Leonie Pauline (2015)
Ph.D (Geology) === The Karoo succession has economic significance through the exploitation of extensive coal deposits and in recent years has seen significant international interest due to potentially large shale gas resources. The thermal history of sedimentary basins affects the genesis of hydrocarbon deposits and it is therefore essential to model and reconstruct the geothermal variation across the Karoo Basin before evaluation of the hydrocarbon resources can take place. The main scientific questions related to the thermal history of the Karoo Basin are whether the emplacement of large volumes of magma was preceded by a large-scale lowgrade thermal doming as proposed for continental rift settings. Alternatively, was the Karoo thermal event restricted to the contact aureole of intrusives, as well as the question whether the intrusion of dolerite resulted in large-scale CO2 or CH4 degassing from coalbeds and carbonaceous shales based on similarities to other large igneous provinces? Magnetic techniques provide an alternative to more traditional methods to study the geothermal history of sedimentary basins (such as illite crystallinity and vitrinite reflectance), which are often associated with significant uncertainty. Three experiments using existing magnetic and palaeomagnetic methods were conducted to determine the peak temperatures reached by Karoo sedimentary rocks before and after the Karoo magmatic event. These experiments include the classic palaeomagnetic baked contact tests (magnetostratigraphy), analyses of the variation of magnetic susceptibility during repeated progressive heating (alteration index method) as well the variation of relative concentrations of fine grained pyrrhotite and magnetite in sedimentary strata relative to their distance from an intrusive (pyrrhotite/magnetite geothermometer). Additionally various magnetic fabric analyses were performed including a study of the variation in anisotropy of magnetic susceptibility (AMS). Although these techniques were successful in delineating the extent of the contact aureoles, only the alternating index (A40) had the ability to give estimated peak temperatures. Results indicate a general elevation of palaeotemperatures of the organic-rich sedimentary rocks of the Ecca Group to temperatures where hydrocarbons are normally converted into gas. Importantly, it is clear from this study that the greatest thermal effects of the sill intrusions on the sedimentary strata are limited to the contact aureoles, suggesting that there is an, as yet unquantified, potential for hydrocarbon resources remaining between these intrusions. A general increase in the palaeotemperatures from southwest to northeast across the basin was observed. This is mainly due to differences in thermal conductivity of the various lithologies across the basin from tight low porosity marine shales in the south and southwest towards more lacustrine mudstone and porous sandstone in the northeast.